Temperature and Redox‐Responsive Hydrogels Based on Nitroxide Radicals and Oligoethyleneglycol Methacrylate. Issue 6 (25th February 2020) - Khodeir, Miriam; Antoun, Sayed; van Ruymbeke, Evelyne; Gohy, Jean‐François
Abstract: A temperature and redox‐responsive polymer hydrogel is constructed by randomly incorporating 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy‐methacrylate (TEMPO) stable nitroxide radicals and oligoethyleneglycol methacrylate (OEGMA) groups in a polymer network. TEMPO can be reversibly oxidized into an oxoammonium cation (TEMPO + ) providing the redox‐responsive properties while the lower critical solubility temperature (LCST) of OEGMA results in temperature‐responsive properties. Since a rather low amount of di(ethylene glycol) dimethacrylate (OEGMA2 ) is used to chemically crosslink the polymer network, the accordingly formed hydrogels obtained after swelling with water consist of microgel particles with entangled polymer chains that are not chemically crosslinked. By varying the amount of TEMPO in the polymer network, it is demonstrated that the radical form of TEMPO aggregates into hydrophobic domains acting as physical crosslinking nodes in the hydrogels and further increasing the cohesion between microgel particles. Increasing the temperature results in two opposite effects on the solubility of TEMPO and OEGMA units. The oxidation of TEMPO into TEMPO + also results in a deep change in the hydrogel properties since TEMPO + units are essentially hydrophilic and do not aggregate into physical crosslinking nodes. Abstract : A temperature and redox‐responsive polymer hydrogel is constructed by randomly incorporating 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy‐methacrylate (TEMPO) stable nitroxide radicals and oligoethyleneglycol methacrylate (OEGMA) groups in a polymer network. TEMPO can be reversibly oxidized into an oxoammonium cation providing the redox‐responsive properties while the lower critical solubility temperature of OEGMA results in temperature‐responsive properties.